The epidemiology and prehospital care of motorcycle crashes in a sub-Saharan African urban center. (2nd October 2020) - Rosenberg, A.; Uwinshuti, F. Z.; Dworkin, M.; Nsengimana, V.; Kankindi, E.; Niyonsaba, M.; Uwitonze, J. M.; Kabagema, I.; Dushime, T.; Krebs, E.; Jayaraman, S.
Abstract: Objective: Road traffic crashes (RTCs) are common among motorcyclists in Kigali, Rwanda. The Service d'Aide Medicale Urgente (SAMU), a prehospital ambulance service, responds to many of these crashes. We aimed to describe motorcycle-related RTCs managed by SAMU. Methods: SAMU clinical data including demographic information, injury characteristics, and management details were analyzed descriptively for all motorcycle crashes occurring between December 2012 and July 2016. Results: Every patient included in this study was injured. These patients all called the ambulance for their injuries after a motorcycle crash. There were 2, 912 motorcycle-related RTCs over the study period, representing 26% of all patients managed by SAMU. The incidence of motorcycle crashes in Kigali was 258 crashes per 100, 000 people over the 3.5-year study period. The average age was 30 years and 80% were males. The most common injuries were to the lower extremities ( n = 958, 33%), head ( n = 878, 30%), or upper extremities ( n = 453, 16%). Injuries often resulted in fractures of extremities ( n = 740, 25%) and external hemorrhage anywhere in the body (unspecified region; n = 660, 23%), yet few were severe based on the Kampala Trauma Score ( n = 23, 2%) and Glasgow Coma Scale ( n = 42, 1.5%). The most common interventions were provision of diclofenac ( n = 1, 526, 52.5%), peripheral intravenous (IV) access ( n = 1, 217, 42%), and administration of IV fluids ( n = 1, 048, 36%). Conclusion: Motorcycle-related RTCs represent a large burden of disease for patients treated by SAMU in Kigali, Rwanda. Young men are most at risk of injury, which imposes a financial strain on society. Though injuries occurred frequently, critical trauma cases from motorcycle crashes were uncommon. This may be a result of several initiatives in Rwanda to improve road safety.